2012
DOI: 10.3892/ol.2012.699
|View full text |Cite
|
Sign up to set email alerts
|

Gastric carcinosarcoma: A case report and review of the literature

Abstract: Abstract. Carcinosarcoma of the stomach is a rare biphasic tumor that consists of both carcinomatous and sarcomatous components. The common carcinoma component is tubular or papillary adenocarcinoma and the mesenchymal sarcomatous components are variable but may include leiomyosarcoma, rhabdomyosarcoma and osteosarcoma. The aim of this study was to describe the characteristics of gastric carcinosarcoma and to present a review of the available literature. We report a case of carcinosarcoma in a 62-year-old fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…Upon review of the literature, 76 cases were identified (Table II) [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. The clinical features of patients with gastric carcinosarcoma appeared to be nonspecific with epigastric pain, weight loss, and melena, as the most common complaints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Upon review of the literature, 76 cases were identified (Table II) [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. The clinical features of patients with gastric carcinosarcoma appeared to be nonspecific with epigastric pain, weight loss, and melena, as the most common complaints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[13][14][15][16] Although the pathogenesis of gastric carcinosarcoma remains controversial, two hypotheses have been Kuroda et al Figure 1 Kuroda et al Figure 2 proposed. 17 The first is the bi-clonal origin hypothesis, which supports the collision tumor theory, according to which the carcinosarcoma originates from two different tumor cell clones. The second is the monoclonal origin hypothesis, whereby the carcinosarcoma originates from a stem cell that can undergo both epithelial and mesenchymal differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…14 The mean survival period is estimated to be 7-10 months. 3,17,22 The most frequently observed distant metastasis site was the liver (Table 1). Reportedly, more than 50% of tumor recurrences occur in the first postoperative year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…clear cell carcinoma of the kidney transforming toward renal sarcoma (26). In immunohistochemical tests the carcinosarcoma yields a positive reaction for cytokeratin in the epithelial (carcinoma) component and a positive reaction for vimentin in the connective tissue (sarcoma) component, which was demonstrated in humans (1,5,6,11,25), and animals (2,12). At the same time, it should be underlined that cancerous cells in the tumour much more frequently yield metastases to lymph nodes than sarcomatous cells do.…”
Section: Neoplastic Transformation Of Ecm Cellsmentioning
confidence: 99%